Reconstruction of temporal and spatial distribution characteristics of sea surface temperature in the Yangtze River Estuary based on dynamic mode decomposition method - Chen, Jiaxing; Jiang, Di; Zhang, Xiaoyu (Zhejiang da xue xue bao. Journal of Zhejiang University. Sciences edition. Li xue ban, 2022)
The characteristics of sea surface temperature distribution in the estuarine and offshore areas are of great significance for understanding natural processes such as ocean thermal and dynamic processes and air sea interaction,as well as the comprehensive results under the influence of human activities.Satellite data reconstruction is an important means to obtain dynamic and accurate sea surface temperature data.This study adopted a dynamic mode decomposition (DMD) for nonlinear systems with sufficient data,It took MODIS\SST data from January 2003 to July 2016,after eliminating the abnormal data and filling in the blank data,the ocean surface temperature data of the Yangtze River Estuary from August 2016 to December 2019 were reconstructed,and the reconstruction effect was evaluated.The research shows that DMD algorithm can solve the sampling problem of dynamic system well provided that the time series data is sufficient.Our results show that DMD algorithm combined with orthogonal right triangular (QR) decompo